Empowerment of Coastal Fishermen Communities Pond in Tambak Osowilangun, Surabaya - Saribulan Z, Re Aprilia; Tasya, Meilana; Casmiwati, Dewi (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Empowerment public is A draft development economy that summarizes values social concepts. This concept produces a new paradigm in development that are people centered, participatory, empowering and sustainability in development. This article used study descriptive with method qualitative . Focus of the research is to see conditions of implementation of coastal communities empowerment in the sub-district Pond Osowilangun, Surabaya City. The approach uses Hasan and Azis (2018) concept in which the empowerment consist of enabling, empowering, and protecting. The results of study describe empowerment community in the area Coast Ward Pond Osowilangun Surabaya from enabling, empowering, and protecting aspects have been fulfilled. It means empowerment in Tambak Osowilangun Surabaya has already realized.